Social media training: The role of the student community for smoking cessation campaign - Dianita Sugiyo; Sutantri Sutantri; Resti Yulianti Sutrisno; Noven Tri Wandasari (ABDIMAS DEWANTARA, 2023)
The prevalence rate of smokers in adolescents in Indonesia is increasing, so it is necessary to hold a program to increase adolescent knowledge about the dangers of smoking. The purpose of this community service is to provide training in managing social media for smoking cessation campaigns to the student community in Yogyakarta. The methods of implementing this community service are; (1) Pretest by looking at the amount of social media reach before the training; (2) Social media content creation training; (3) Instagram live about the dangers of smoking; (4) Post-test by looking at the amount of social media reach after the training. The results of the training program showed that the number of social media reach for smoking cessation campaigns has increased.